Integration of Nutrition and Crop Protection Products: Crop nutrition and protection - Kadyampakeni, Davie Mayeso; Johnson, Evan (EDIS, 2022)
In the era of citrus greening disease (or huanglongbing, HLB), it is critical to maintain optimal nutrition and disease/pest management strategies in citrus to avoid adverse effects on tree performance. Improved fertilizer blends are commercially available along with crop protection products for mitigating pests and diseases. We conducted a study near the Citrus Research and Education Center, Lake Alfred in the past 4 years to determine if plant nutritional fertilizer sources coupled with specific crop protection chemicals help mitigate HLB and other citrus diseases. Results indicate improved canopy, fruit yield and juice quality along with root health due to integrated use of improved fertilizer blends and crop protections products.